2014
DOI: 10.2478/pjvs-2014-0091
|View full text |Cite
|
Sign up to set email alerts
|

A 34-year retrospective study of equine viral abortion in Poland

Abstract: The purpose of the present review was a comparison of the abortions caused by EAV and EHV-1 viruses over the 34 years. A total of 452 tissues samples from aborted fetuses (347) or foals (105) stillborn or newborn that died within 72 hours were investigated. The material for the examinations came from different farms located throughout Poland. The tissue homogenates were examined by using virus isolation test in RK-13 and Vero cell lines and the cytopathic agent was confirmed as EHV-1 by the direct fluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Equid alphaherpesvirus 1 is traditionally recognized as an important agent involved in equine abortion. Levels of EHV-1 abortion reported in the 1990s varied from 8.3 to 40% (TENGELSEN et al, 1997;BAŻANÓW et al, 2014;SCHULTHEISS et al, 1993). More recent studies have pointed to lower rates of EHV-1: 6.9% in France (LAUGIER et al, 2011), 6.5% in the United Kingdom (SMITH et al, 2203), 16% in Hungary (SZEREDI et al, 2008), 10.1% in Japan (MURASE et al, 2017 and 8.9% in Germany (WEBER et al, 2018).…”
Section: Total 105mentioning
confidence: 99%
See 2 more Smart Citations
“…Equid alphaherpesvirus 1 is traditionally recognized as an important agent involved in equine abortion. Levels of EHV-1 abortion reported in the 1990s varied from 8.3 to 40% (TENGELSEN et al, 1997;BAŻANÓW et al, 2014;SCHULTHEISS et al, 1993). More recent studies have pointed to lower rates of EHV-1: 6.9% in France (LAUGIER et al, 2011), 6.5% in the United Kingdom (SMITH et al, 2203), 16% in Hungary (SZEREDI et al, 2008), 10.1% in Japan (MURASE et al, 2017 and 8.9% in Germany (WEBER et al, 2018).…”
Section: Total 105mentioning
confidence: 99%
“…A study covering 1977-2010 in Poland found rates of 25.6% for EHV-1 (BAŻANÓW et al, 2014). The authors also report that the rates of isolation of the two viruses were inversely proportional, but most laboratories do not usually include them in routine differential diagnosis of equine abortion or foal death.…”
Section: Total 105mentioning
confidence: 99%
See 1 more Smart Citation
“…Equine herpesviruses have worldwide distribution including Poland [ 6 , 34 ]. However, EHV-1 detection in Poland has been reported mainly as part of diagnostic investigations of cases of abortion or neonatal death [ 35 38 ] and no data are currently available on the frequency of detection of EHV-1/4 among other groups of horses. The only virological survey of EHV-2 among Polish horses was conducted approximately 15 years ago [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Equid alphaherpesvirus 1 (formerly called equine herpesvirus 1, EHV-1) is one of the main infectious causative agents of abortion in mares [ 1 ]. Infection with EHV-1 can also be associated with stillbirth, neonatal foal death, rhinopneumonitis in young horses and a neurological disorder called equine herpesvirus myeloencephalopathy (EHM) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%